2015
DOI: 10.4103/2228-7477.150440
|View full text |Cite
|
Sign up to set email alerts
|

99m Tc-phytate lymphoscintigraphy for detection of sentinel node: Preliminary results of the first year′s clinical experience in Isfahan, Iran

Abstract: Sentinel lymph node is the first regional lymph node that drains the lymph from the primary tumor. It is potentially the first node to receive the seeding of lymph-borne metastatic cells. This study aimed to discuss lymphoscintigraphy procedural guidelines for detection of sentinel node using 99mTc-Phytate in Isfahan, Iran. Moreover, the preliminary results of the first year's clinical experience of lymphoscintigraphy in Isfahan, Iran are also presented. A total of 36 consecutive sentinel node procedures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Most SLNs in patients who did not demonstrate SLNs on imaging were eventually identified intraoperatively either by blue dye or a hand-held gamma detector. Studies directly comparing Tc-99m phytate with other colloid radiotracers also showed noninferiority of Tc-99m phytate in terms of the imaging and the intraoperative nodal detection rate, which supports our study findings [21222324]. Although the use of Tc-99m phytate is largely restricted in certain Asian countries, current evidence suggests that it is quite adequate for SLN mapping and should suffice in hospitals performing breast cancer surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most SLNs in patients who did not demonstrate SLNs on imaging were eventually identified intraoperatively either by blue dye or a hand-held gamma detector. Studies directly comparing Tc-99m phytate with other colloid radiotracers also showed noninferiority of Tc-99m phytate in terms of the imaging and the intraoperative nodal detection rate, which supports our study findings [21222324]. Although the use of Tc-99m phytate is largely restricted in certain Asian countries, current evidence suggests that it is quite adequate for SLN mapping and should suffice in hospitals performing breast cancer surgery.…”
Section: Discussionsupporting
confidence: 88%
“…The injection dose, nonetheless, is reasonably regarded as a predictive variable because higher injected radioactivity theoretically produces a more intense signal from the SLN and hence is easier to detect by a gamma camera. Although most studies used a radioactivity dose <1.0 mCi, our study results imply that a 2.0 mCi total radioactivity dose might achieve a better detection rate when Tc-99m phytate is used [142223242526]. This phenomenon can be endorsed by the hypothesis we propose.…”
Section: Discussionsupporting
confidence: 61%
“…The radiation dose estimation is the basis for the use of radiopharmaceuticals in nuclear medicine, and it is also the first step in protection against radiation. For example, in therapeutic applications of radiopharmaceuticals, it is necessary to assess the absorbed dose in the tumor and normal tissues to choose the most appropriate treatment protocol, maintaining doses to vital organs at safe levels [1].…”
Section: Introductionmentioning
confidence: 99%